The Project-Based Learning Development Module in the Learning of Heavy Equipment in Post-Pandemic in Improving Students' Cognitive and Psychomotor Skills - Toto Sugiarto; Nizwardi Jalinus; Rijal Abdullah; Ridwan Ridwan; Dwi Sudarno Putra; Muslim Muslim (VANOS Journal of Mechanical Engineering Education, 2023)
Learning requires supporting materials in the form of reliable teaching materials, one of which can be in the form of learning modules. So it is necessary to add project-based learning modules for the development of existing modules. The purpose of this research is to measure the validity, practicality, and effectiveness in the development of project-based heavy equipment technology modules. This research is included in the research and development (R&D) category, the ADDIE principle is used in this research model. Lecturers and students in automotive engineering were used as research subjects. The results of the project-based heavy equipment technology module development research fulfill the requirements of validity, practicality, and effectiveness. In its implementation, the validity aspect of module development scored 89.07% with very valid criteria, the practicality aspect scored 87.92% with very practical criteria. The knowledge test and skills test showed the effectiveness of module development, the results of the knowledge and skills test on 30 students achieved an average score of 86.67% with very high criteria.